Theatre History and Performance: the Archive’s Unruliness as Method - Pinto (Universidade Católica Portuguesa – Lisbon, Portugal), Isabel (Revista Brasileira de Estudos da Presença, 2022)
By reviewing the notion of archive (Derrida, 1995) that underlies Theatre History research, performance is here presented as a new methodological insight. As such, it allows for a cross disciplinary look into the historical sources, and, at the same time, a renewed embodiment of cultural heritage. This latter aspect, here illustrated by the description of three performances, relates to the international initiative performing the archive (Osthoff, 2009; Jackson; Kidd, 2011; Borggreen; Gade, 2013), which aims at both the public and social dimension and the transformative dynamics of cultural heritage.